Synthetic microbial community SMC-L1 optimizes flavor chemistry in reduced salt soy sauce via targeted metabolic reprogramming - Gao, Yuqi; Zhang, Lin; Zhang, Yi; Huang, Jun; Wu, Chongde; Zhou, Rongqing (Frontiers in Microbiology, 2025)
The high sodium content in traditional soy sauce presents significant public health concerns, particularly related to hypertension and cardiovascular diseases. However, reducing salt content often disrupts microbial ecology and impairs flavor formation during fermentation. To overcome this challenge, we developed synthetic microbial communities (SynMCs) for reduced-salt (13% NaCl) moromi fermentation under traditional sun-brewing conditions. Using integrated multi-omics analyses, we identified an optimal consortium (SMC-L1) incorporating Tetragenococcus halophilus T10 as a key lactic acid bacterium alongside functional yeast strains. This defined community maintained fermentation stability while significantly enhancing flavor-relevant biochemical profiles. SMC-L1 inoculation markedly improved key quality parameters, increasing total nitrogen by 40.8% and amino acid nitrogen by 56.7%. Furthermore, it elevated critical metabolites including organic acids, particularly succinate, free amino acids, and short-chain esters. Network analysis revealed robust ecology-metabolite relationships: Tetragenococcus abundance correlated with succinate production and ester synthesis, while Aspergillus dynamics corresponded with free amino acid accumulation. These findings highlight how targeted microbial consortia can reprogram metabolic networks under salt-reduced conditions. From a food microbiology perspective, this study demonstrates that rational design of microbial communities can effectively decouple salt reduction from flavor deterioration in fermented foods. The metabolic pathways observed, particularly the anaerobic TCA cycle activity connecting Tetragenococcus to succinate accumulation, provides mechanistic insights into microbial adaptation to reduced-salt environments. This approach offers a viable strategy for developing healthier fermented products without compromising their sensory characteristics, advancing both fundamental knowledge and practical applications in food biotechnology.